Curriculum Innovation in Private Higher Education Institutions by Integrating Project-Based Learning to Enhance Students' Career Readiness - Handayani, Lisa; Haeruddin, Haeruddin (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Several Private Higher Education Institutions (PHEIs) in Indonesia are innovating by integrating Project-Based Learning (PBL) to enhance student job readiness and meet the evolving demands of the labor market and industry. PBL allows students to apply theoretical knowledge in real-world contexts while developing essential 21st-century skills such as critical thinking, creativity, and collaboration. This study combined a comprehensive literature review of global PBL trends and best practices including models from MIT, Stanford, the Erasmus program, Australia, and Finland with case studies involving interviews with faculty, students, and industry representatives. Findings show that PBL significantly improves student skills and curriculum relevance through strengthened academic-industry collaboration: 85% of students reported gains in practical skills like project management, 78% improved professional skills such as communication and work ethic, 90% advanced technical skills, and 75% enhanced non-technical skills including teamwork and leadership. From the industry perspective, 80% of companies rated PBL-trained graduates as more job-ready, with 70% noting faster adaptation to workplace demands. Successful PBL implementation depends on faculty empowerment, adequate infrastructure, and strong industry partnerships, though challenges such as limited resources and the need for ongoing faculty development remain. These results support recommendations for curriculum reform and policy development focused on structured project modules, expanded industry collaboration, and continuous educator training, positioning PBL as a vital approach to bridging theory and practice and aligning higher education with modern labor market needs.